Benchmark dose analyses of toxic endpoints in lung cells provide sensitivity and toxicity ranking across metal oxide nanoparticles and give insights into the mode of action. (1st October 2020) - Pink, Mario; Verma, Nisha; Schmitz-Spanke, Simone
Highlights: Benchmark dose (BMD) analysis is an effective tool to rank sensitivity and toxicity. BMD analysis was used to support modes of action basing on endpoint assays. BEAS-2B reacted more sensitively to exposure to nanosized metal oxides as A549. Abstract: Introduction: The benchmark dose (BMD) is a dose that produces a predetermined change in the response rate of an adverse effect. This approach is increasingly utilized to analyze quantitative dose-response relationships. To proof this concept, statistical analysis was compared with the BMD approach in order to rank the sensitivity as well as the toxicity and to describe the mode of action. Methods: Bronchial (BEAS-2B) and alveolar epithelial cells (A549) were exposed to a wide concentration range (0.4–100 μg/mL) of five metal oxide nanoparticles (CeO2, CuO, TiO2, ZnO, ZrO2 ). Eight toxicity endpoints were determined representing integrity of lysosomal and cell membrane, oxidative stress level, glutathione based detoxification (glutathione S-transferase), oxidative metabolism (cytochrome P450), alteration of the mitochondrial membrane potential, alteration of phase II antioxidative enzyme (NAD(P)H:quinone oxidoreductase), and de novo DNA synthesis. Results: Based on the BMD calculated for the most sensitive test, the toxicity decreased in the following order: ZnO > CuO > TiO2 >ZrO2 >CeO2 in BEAS-2B. Both statistical evaluation methods revealed a higher sensitivity of BEAS-2B cells. The BMD-derived mode of action for CuO confirmed the existing hypotheses and provided insights into less known mechanisms. Conclusion: The findings proofed that BMD analysis is an effective tool to evaluate different aspects of risk assessment.